Kajian Sosiolinguistik Terhadap Ujaran Bahasa Mahasiswa Program Studi Bahasa Indonesia Semester Tiga - Fenesiana Claudina Eunike Tabun; Desantri Bouk Mali; Mersiana Luruk Klau; Yustina Sako (Pusat Riset dan Inovasi Nasional, 2024)
The use of language in life greatly affects articulation in communicating and interacting with humans. This interaction provides a unity in connecting a difference. Therefore, diversity in language becomes its own uniqueness in the field of communication. The important role of communication tools helps the articulation of social life. The use of language in educational institutions, is very vulnerable to be influenced by the surrounding environment. This causes the dialect mix used by the third Semester Indonesian education students is very unique and diverse. In general, this study aims to determine the diversity of languages used by various students in educational institutions and their environments, especially students of the third Semester of Indonesian Education Study Program specifically, the purpose of this article is made to (1) Describe the dialect of the speech of Indonesian students in the third Semester, and (2) describe the use of mixed code against Indonesian students in the third Semester. The study used descriptive qualitative methods as a research method and sociolinguistic approach. The research was conducted in order to solve problems that often occur in the field by using several stages of Data Collection (1) taking samples of language speech used by Indonesian students in the third Semester, (2) analyzing the use of dialect and coding against the language speech of Indonesian students in the third Semester. Thus, the results of the study showed that the proven use of dialect and mix code in communicating that is often used by students of the third Semester of Indonesian. This study also describes the linguistic behavior of the third Semester Indonesian students directly through oral.